The politics of space architecture, painting, and theater in postmodern Germany - Nash, Douglas 1962- (American university studies. Germanic languages and literature, 1996)
"This multigeneric study applies a spatial terminology to three well-known German-speaking artists: architect Hans Hollein, painter Anselm Kiefer and dramatist Heiner Muller. It explores their efforts to place themselves, sometimes critically, within the confusing and commodified landscape of postmodern culture. Along the way, the study indicates the difficulty for progressive cultural activity today." -- Provided by publisher